The presentation of Culture in EFL - Blilo , Mirvat (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research deals with two different views on teaching the target language in relation to its own culture. The first view refers to the inevitability of teaching culture through language as there is a strong tie between the two issues. The second view points out that the cultural identity and values of EFL learners are threatened while acquiring a foreign language. These are referred to in this paper as the positive view and the counter-argument. Some suggestions are then presented concerning the use of cultural elements in classrooms. The last part discusses one task taken from a textbook followed by an option to modify them to become more culture-oriented.